Archetypal Allegory: Harry Potter as the Modern-day Moses. A Comparative Study - YAGOUBI Messaouda; DJAAFER Amira (UNIVERSITY OF MOHAMED BOUDIAF- M’SILA, 2024)
This dissertation employs Archetypal Criticism to explore the portrayal of Harry Potter as a modern-day Prophet Moses in J.K. Rowling's renowned series. Through a comparative analysis, it delves into the shared Hero archetype manifested in both Potter and Moses’s narratives , unraveling their parallel journeys of destiny, adversity, and redemption. Drawing from mythological and religious symbolism, this study examines how Potter embodies characteristics of Moses (peace be upon him), such as his call to adventure, the guidance of mentors, and the confrontation of dark forces. By examining the narrative structure, character development, and thematic elements, this research clarifies the profound resonance between the two figures across religious, cultural and historical contexts. Ultimately, it argues that Harry Potter serves as a contemporary embodiment of the timeless Hero archetype, echoing the enduring significance of mythological motifs in shaping cultural narratives and identities
Keywords: Harry Potter; Moses; Archetypal Criticism; Hero archetype; modern-day Moses.